1997
DOI: 10.1207/s15327752jpa6801_6
|View full text |Cite
|
Sign up to set email alerts
|

The MCMI--III: Present and Future Directions

Abstract: Both the original Millon Clinical Multiaxial Inventory (MCMI-I; Millon, 1977) and the Millon Clinical Multiaxial Inventory-II (MCMI-II; Millon, 1987) were refined and strengthened on a regular basis by both theoretic logic and research data. This aspiration has continued. The new Millon Clinical Multiaxial Inventory-III (MCMI-III; Millon, 1994) has been further coordinated with the most recent official diagnostic schema, the Diagnostic and Statistical Manual of Mental Disorders (4th ed., [DSM-IV]; American Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 0 publications
2
119
0
1
Order By: Relevance
“…Histrionic, Narcissistic, Antisocial, and Borderline scales scores were used for statistical comparison between groups. Number of items and Cronbach's alpha for each scale were as follows in the Spanish adaptation of the MCMI-III (Millon, Davis, & Millon, 2007): Histrionic (17 items, ␣ = .80), Narcissistic (24 items, ␣ = .70), Antisocial (17 items, ␣ = .76), and Borderline (16 items, ␣ = .82). Means and standard deviations for the scale in each group of batterers are presented in Table 1.…”
Section: Individual Variables Personality Participants Completed Thementioning
confidence: 99%
“…Histrionic, Narcissistic, Antisocial, and Borderline scales scores were used for statistical comparison between groups. Number of items and Cronbach's alpha for each scale were as follows in the Spanish adaptation of the MCMI-III (Millon, Davis, & Millon, 2007): Histrionic (17 items, ␣ = .80), Narcissistic (24 items, ␣ = .70), Antisocial (17 items, ␣ = .76), and Borderline (16 items, ␣ = .82). Means and standard deviations for the scale in each group of batterers are presented in Table 1.…”
Section: Individual Variables Personality Participants Completed Thementioning
confidence: 99%
“…This suggested that the instrument's predictive validity could be improved. Millon, Davis and Millon (1997) however report very different positive predictive validities, ranging from .33 (delusional) to .93 (drug abuse), with an average of .64 across all PD and axis 1 disorders. Millon et al (1997) also report Kappa levels ranging from .23 (anxiety) to .84 (paranoid), suggesting highly discrepant levels of test-retest reliability.…”
Section: Continuedmentioning
confidence: 99%
“…Therefore, the SCATI is an instrument of value for further research (Watson & Sinha, 2007) Retzlaff (1996) found the MCMI-III's predictive power to range between .00 to .32, however Millon et al (1997) Trull, et al,1993).…”
mentioning
confidence: 99%
“…5.3.4. Millon Clinical Multiaxial Inventory (MCMI;Millon and Davis, 1997) The original MCMI is a 175-item, true-false inventory. For the present purposes, the major depression, anxiety, alcohol abuse, and drug abuse subscales were used as covariates.…”
Section: Psychosocial Historymentioning
confidence: 99%